FINANCIAL DISTRESS AND DEMOGRAPHIC PROFILE AS PREDICTORS OF GENERAL WEIGHTED AVERAGE OF FIRST-GENERATION COLLEGE STUDENTS AT CEBU INSTITUTE OF TECHNOLOGY-UNIVERSITY - Felise Kirsten Marie S. Villa, KC Joy R. Sampan, Martine Jane A. Socobos, Joselito O. Banono Jr. (Chelonian Research Foundation, 2024)
Abstract - Academic performance is vital in education, and it is evaluated through marks and goals set by students and teachers, often measured by general weighted averages (GWA). First-generation college students (FGCS) of various demographic backgrounds face challenges like financial distress impacting their academic performance and overall academic journey. This study aimed to determine the influence of demographic profile and financial distress on the general weighted average of first-generation college students at Cebu Institute of Technology-University for the academic year 2023 to 2024. It addressed the gaps in understanding how demographic factors and financial distress impacted the academic success of first-generation college students. Participants were 68 first-generation college students (FGCS) identified through complete enumeration. The research utilized a researcher-made Demographic Profile Questionnaire, the InCharge Financial Distress/Financial Well-Being (IFDFW) Scale, and the GWA during the first semester of the academic year 2023 to 2024. Findings showed that most students were predominantly female, aged 18 to 20, and from lower-middle-income families. Financial distress levels varied, with a majority reporting moderate. Most first-generation college students achieved a “very good” GWA classification, reflecting good academic performance. Analysis indicated a significant model with financial stress and demographic profile as predictors of the GWA of the FGCS. This study’s recommendation highlights the need for support services, inclusive campus cultures, and comprehensive strategies to address financial distress among these students.